Factor (4j-2)^2 - (2+4j)^2 and 4(5b-3)^2 +10(5b-3) - 6

1 Answer | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The expression (4j-2)^2 - (2+4j)^2 is of the form a^2 - b^2 = (a - b)(a + b)

It can be factored as:

(4j-2)^2 - (2+4j)^2 = (4j - 2 - 2 - 4j)(4j - 2 + 2 + 4j)

=> -4*(8j)

4(5b-3)^2 +10(5b-3)-6

Let 5b - 3 = y

=> 4y^2 + 10y - 6

=> 4y^2 + 12y - 2y - 6

=> 4y (y + 3) - 2(y + 3)

=> (4y - 2)(y + 3)

=> (4(5b - 3) - 2)(5b - 3 + 3)

=> (20b - 14)(5b)

=> (10b - 7)(10b)

The factorized form of (4j-2)^2 - (2+4j)^2 = -4*(8j) and 4(5b-3)^2 +10(5b-3)-6 = (10b - 7)(10b)

We’ve answered 318,990 questions. We can answer yours, too.

Ask a question